2019
DOI: 10.1016/j.immuni.2019.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Cancer: Triggers, Mechanisms, and Consequences

Abstract: Inflammation predisposes to the development of cancer and promotes all stages of tumorigenesis. Cancer cells, as well as surrounding stromal and inflammatory cells, engage in well-orchestrated reciprocal interactions to form an inflammatory tumor microenvironment (TME). Cells within the TME are highly plastic, continuously changing their phenotypic and functional characteristics. Here, we review the origins of inflammation in tumors, and the mechanisms whereby inflammation drives tumor initiation, growth, prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
1,922
3
20

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,556 publications
(1,972 citation statements)
references
References 184 publications
27
1,922
3
20
Order By: Relevance
“…In the early stage of tumorigenesis, inflammatory cells can become influential tumor promoters, creating a favorable environment for tumor growth and promoting blood vessel growth [17][18][19]. Many factors have been found to be related to the occurrence of MVI in HCC; in this study, it is suggested that GLR is positively correlated with AST, and NEUT, AST, GLR and other inflammatory factors' level in the MVI group are higher than those in the non-MVI group, suggesting that these inflammatory factors may promote HCC progression and increase risk of MVI, which is in accordance with the researches which illuminate that anti-inflammatory treatment can effectively prevent early tumorigenesis and later malignant transformation [20,21] .…”
Section: Discussionsupporting
confidence: 88%
“…In the early stage of tumorigenesis, inflammatory cells can become influential tumor promoters, creating a favorable environment for tumor growth and promoting blood vessel growth [17][18][19]. Many factors have been found to be related to the occurrence of MVI in HCC; in this study, it is suggested that GLR is positively correlated with AST, and NEUT, AST, GLR and other inflammatory factors' level in the MVI group are higher than those in the non-MVI group, suggesting that these inflammatory factors may promote HCC progression and increase risk of MVI, which is in accordance with the researches which illuminate that anti-inflammatory treatment can effectively prevent early tumorigenesis and later malignant transformation [20,21] .…”
Section: Discussionsupporting
confidence: 88%
“…Tumor-associated immune cells and their crosstalk with cancer and the components of its microenvironment dramatically affect tumor behavior and patient outcome [1,2]. The concept of cancer immunoediting, represents the dynamic of this interaction, which runs through the phases of elimination, equilibrium and escape, and explains how immunosuppression can overwhelm immunosurveillance [3], eliciting the development of immunological-based approaches to cancer treatment [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Colon cancer, like some other solid malignancies, is infiltrated by various types of immune cells such as tumor-associated macrophages (TAMs), monocytes, neutrophils, and mast cells, which contribute to an inflammatory microenvironment (Greten & Grivennikov, 2019;Komohara, Fujiwara, Ohnishi, & Takeya, 2016). Inflammatory microenvironment can regulate cancer progression and affect many facets of cancer development, including cell proliferation, angiogenesis, invasion, and metastasis (Greten & Grivennikov, 2019). TAMs are a well-known component of inflammatory infiltrates and key producer of inflammatory cytokines and chemokines (Pathria, Louis, & Varner, 2019).…”
Section: Introductionmentioning
confidence: 99%